Motor neuron expression of the voltage-gated calcium channel cacophony restores locomotion defects in a Drosophila, TDP-43 loss of function model of ALS. - Chang, J.C.; Hazelett, D.J.; Stewart, J.A.; Morton, D.B. (Brain Research, 2014)
Dysfunction of the RNA-binding protein, TDP-43, is strongly implicated as a causative event in many neurodegenerative diseases including amyotrophic lateral sclerosis (ALS). TDP-43 is normally found in the nucleus and pathological hallmarks of ALS include the presence of cytoplasmic protein aggregates containing TDP-43 and an associated loss of TDP-43 from the nucleus. Loss of nuclear TDP-43 likely contributes to neurodegeneration. Using Drosophila melanogaster to model TDP-43 loss of function, we show that reduced levels of the voltage-gated calcium channel, cacophony, mediate some of the physiological effects of TDP-43 loss. Null mutations in the Drosophila orthologue of TDP-43, named TBPH, resulted in defective larval locomotion and reduced levels of cacophony protein in whole animals and at the neuromuscular junction. Restoring the levels of cacophony in all neurons or selectively in motor neurons rescued these locomotion defects. Using TBPH immunoprecipitation, we showed that TBPH associates with cacophony transcript, indicating that it is likely to be a direct target for TBPH. Loss of TBPH leads to reduced levels of cacophony transcript, possibly due to increased degradation. In addition, TBPH also appears to regulate the inclusion of some alternatively spliced exons of cacophony. If similar effects of cacophony or related calcium channels are found in human ALS patients, these could be targets for the development of pharmacological therapies for ALS. This article is part of a Special Issue entitled RNA Metabolism 2013.